Early remodelling of coronary stenoses after thrombolytic treatment in patients with acute myocardial infarction. Issue 3 (September 1995) - Tousoulis, D.; Andreotti, F.; Hackett, D.; Haider, A. W.; Maseri, A.; Davies, G.
Abstract : OBJECTIVE--To assess the frequency of early remodelling of coronary stenosis morphology after thrombolytic treatment in patients with acute myocardial infarction. DESIGN--Coronary angiograms were analysed by a computerised edge detection analysis system. Coronary stenosis severity was measured and morphology classified as smooth or complex. PATIENTS--Coronary arteriograms were obtained approximately 90 min and 24 h after thrombolytic treatment from 40 patients with acute myocardial infarction. MAIN RESULTS--Stenosis morphology was complex in 22 patients (65%) and smooth in 11 (32%) 90 min after thrombolysis. The morphology of 11 (50%) complex coronary stenoses and three (27%) smooth stenoses had changed at 24 h (P < 0.05). The transition from complex to smooth was associated with a reduction in stenosis severity from 65 (4)% to 51 (5)% (P < 0.05). The stenosis severity was 63 (4)% and 60 (5)% in those with persistently complex morphology, and 56 (7)% and 50 (5)% in those with persistently smooth morphology at 90 min and 24 h respectively (NS). CONCLUSIONS--Transition of morphology from complex to smooth within 24 h is common. This transition is associated with a reduction in stenosis severity of a degree greater than that found in persistently smooth stenoses over the same interval. 50% of stenoses are smooth at 24 h.